Ornamental Patterns of Contemporary Indonesian Batik: Clothing for Strengthening the Articulation of Appearance Characteristics - Setyo Budi,; Tiwi Bina Affanti,; Sayid Mataram, (Wacana Seni Journal of Arts Discourse, 2024)
Batik is a significant aspect of Javanese and Indonesia culture, celebrated for its complex motifs, rich history, and deep cultural values. The research method used is qualitative research based on exploration and explanation supported with Iconographical Analysis and Elegant Design Theory. UNESCO’s recognition of batik as a world culture heritage, has led to a revival in interest and respect for this art form in Indonesia. Historically, batik was reserved for the nobility, but nowadays, it has evolved into national attire with contemporary significance. The focus of this study is to position batik as not only a traditional work of art that has developed into contemporary fashion, but also contains various ethical and aesthetic boundaries as a reflection of the intelligence of clothing culture. Contemporary batik is seen as a medium that can enhance the wearer’s appearance. Several characteristics of a person’s appearance that can be strengthened based on batik ornamental patterns are authoritative, openness, responsible, dynamic, and simplicity. This pattern is actualised in fashion design with a format resembling the letters or punctuation marks of Y, +, \, Z, and I.